Efficacy of the self-interrogation strategy for developing reflective thinking and learning some basic basketball skills in second intermediate grade students - Khalid Awaad, Ahmed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
This study aimed to identify the effect of the self-interrogation strategy in developing reflective thinking and learning some basic basketball skills in fifth-grade students through preparing educational units according to this strategy. With this purpose, the researcher used an experimental design. In the present study, the participants were allocated into two groups, i.e. the experimental group and the control group. The participants of the experimental group received training by the self-interrogation strategy. The participants of the control group continued their studies in the traditional way. The researcher used the appropriate statistical methods to extract the results. Based on the findings of the present study, the researcher concluded that the educational approach used in the experimental group (the self-interrogation strategy) and the curriculum followed by the control group are effective methods in developing the specific basic skills in basketball. However, the students of the experimental group outperformed the students of the control group in the development of reflective thinking and the development of basketball basic skills.